Mindfulness meditation in the treatment of substance use disorders and preventing future relapse: neurocognitive mechanisms and clinical implications - Priddy SE; Howard MO; Hanley AW; Riquino MR; Friberg-Felsted K; Garland EL (Dove Medical Press, 2018)
Sarah E Priddy,1,2 Matthew O Howard,3 Adam W Hanley,1,2 Michael R Riquino,1,2 Katarina Friberg-Felsted,4 Eric L Garland1,2 1College of Social Work, Center on Mindfulness and Integrative Health Intervention Development, University of Utah, Salt Lake City, UT, USA; 2College of Social Work, University of Utah, Salt Lake City, UT, USA; 3School of Social Work, University of North Carolina, Chapel Hill, NC, USA; 4College of Nursing, University of Utah, Salt Lake City, UT, USA Abstract: Substance use disorders (SUDs) are a pervasive public health problem with deleterious consequences for individuals, families, and society. Furthermore, SUD intervention is complicated by the continuous possibility of relapse. Despite decades of research, SUD relapse rates remain high, underscoring the need for more effective treatments. Scientific findings indicate that SUDs are driven by dysregulation of neural processes underlying reward learning and executive functioning. Emerging evidence suggests that mindfulness training can target these neurocognitive mechanisms to produce significant therapeutic effects on SUDs and prevent relapse. The purpose of this manuscript is to review the cognitive, affective, and neural mechanisms underlying the effects of mindfulness-based interventions (MBIs) on SUDs. We discuss the etiology of addiction and neurocognitive processes related to the development and maintenance of SUDs. We then explore evidence supporting use of MBIs for intervening in SUDs and preventing relapse. Finally, we provide clinical recommendations about how these therapeutic mechanisms might be applied to intervening in SUDs and preventing relapse. Keywords: addiction, mindfulness, reward, relapse, substance use disorders